The Analisis Teologis Konsep Pengharapan Kepada Tuhan Dalam Kitab Mikha 7:7 - Yermia Miliwati; Ferniati Kadang Tanrigoa (Jurnal Teologi Amreta (ISSN: 2599-3100), 2025)
The purpose of this study is to theologically analyze the concept of hope in God in the book of Micah. Methods used. The research method used is a qualitative research method with literature study and text analysis. The results of the study indicate that hope in the Book of Micah is not an escape from reality, but an active belief that a just God is also a faithful God to save. This hope is born from God's unchanging faithfulness. In conclusion, the Book of Micah reveals the tension between judgment and hope, affirming that even though God's people have fallen into sin and injustice, God still acts as a just Judge and a faithful Redeemer. God's judgment is not merely punishment, but also a means of purification that opens up space for restoration. In this context, hope is born not from human strength, but from God's unchanging faithfulness. In the midst of suffering due to sin and oppression, the book of Micah voices a call to continue to believe and rely on God. Micah does not cover up the reality of suffering, but rather shows that in suffering people are invited to return to God with broken and repentant hearts. Hope is a response of faith that arises from the awareness that God sees the suffering of His people and will act according to His time and plan.